2017
DOI: 10.5664/jcsm.6764
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Pregnancy Is Associated With Depressive Symptoms and Eating at Night

Abstract: Study Objectives: Deterioration in sleep quality seems to be a natural consequence of physical changes during pregnancy. It is still unclear if insomnia in pregnancy is associated with the same factors as chronic insomnia in the general population. The aim of this study was to explore the determinants of insomnia during pregnancy. Methods: The study included 266 women (mean age: 30.6 ± 5 years, weeks of pregnancy: 36 [interquartile range 32-38]) recruited at the Department of Gynecology and Obstetrics, Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 34 publications
4
45
0
2
Order By: Relevance
“…The prevalence rate of 32.5% obtained in this study represents almost a third of all the respondents. This rate is comparable to similar studies done in this environment and other places with reported prevalence rate between 35.5% and 47.3% [6,7]. But much lower than rates of 56.1% and 61.6% reported from studies among Chinese and Norwegian pregnant women respectively [4,5].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalence rate of 32.5% obtained in this study represents almost a third of all the respondents. This rate is comparable to similar studies done in this environment and other places with reported prevalence rate between 35.5% and 47.3% [6,7]. But much lower than rates of 56.1% and 61.6% reported from studies among Chinese and Norwegian pregnant women respectively [4,5].…”
Section: Discussionsupporting
confidence: 85%
“…While a recent study done in Norway reported a higher prevalence of 61.6% [5]. In a more recent study done in 2017 in warsaw, a prevalence rate of 39.8% was reported among women in their last trimester [6]. A similar study done in Nigeria reported a prevalence rate of 47.3% with more cases of insomnia occurring during the 3 rd trimester of pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is gaining recognition as an important factor to consider when studying or treating pregnant women. For example, many epidemiological reports have linked poor sleep or insomnia to poor health outcomes, including depression (Okun, Kiewra, Luther, Wisniewski, & Wisner, 2011;Okun, Kiewra, Luther, et al, 2011;Volkovich, Tikotzky, & Manber, 2016;Wolynczyk-Gmaj et al, 2017;Yang et al, 2017;Hux, Roberts, & Okun, 2017), preterm birth (Okun, Luther, Prather, et al, 2011;Blair, Porter, Leblebicioglu, & Christian, 2015;Li et al, 2016) and longer labor times (Evans, Dick, & Clark, 1995;Lee & Gay, 2004). The undisputed association between stress and sleep is particulary poignant in pregnancy, as stress is independently associated with poor pregnancy outcomes (Okun, Roberts, Begley, Catov, & Patrick, 2013;Palagini et al, 2014;Hux et al, 2017).…”
Section: Overview Of Sleepmentioning
confidence: 99%
“…With regard to infant outcomes, our knowledge is even more limited. Historically, the emphasis has been on sleep-disordered breathing (SDB) or sleep apnea and infant outcomes (Bourjeily et al, 2010;Chen et al, 2012;Franklin et al, 2000;Koken et al, 2007;Tauman et al, 2011); however, recent data have emphasized sleep quality and insomnia and how they impact the neonate (Dorheim et al, 2012;Okun, Kiewra et al, 2011;Okun et al, 2015;Rognmo, Sivertsen, & Eberhard-Gran, 2016;Sivertsen, Hysing, Dorheim, & Eberhard-Gran, 2015;Wolynczyk-Gmaj et al, 2017).…”
Section: Sleep and Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Hyperarousal has also been related to depression. Szelenberger and Niemcewicz [9] found correlations between hyperarousal and depression scores, demonstrating relationships with the cognitive and affective aspects of depression; moreover, depressive symptoms and night eating were key factors related to insomnia [10]. Higher levels of self-reported arousal were associated with distress from interpersonal problems; individuals with insomnia who reported more distress from interpersonal problems tended to have more severe insomnia and cognitive pre-sleep arousal, possibly due to rumination [11].…”
Section: Introductionmentioning
confidence: 99%